2020
DOI: 10.1021/acs.jpcc.0c04510
|View full text |Cite
|
Sign up to set email alerts
|

Practical Aspects of Recording Ultra-Wideline NMR Patterns under Magic-Angle Spinning Conditions

Abstract: Many NMR-active nuclei give rise to solid-state NMR spectra that span extremely large frequency regions due to the effects of large anisotropic NMR interactions; such spectra, which can range from 250 kHz to several MHz in breadth, have been termed ultrawideline (UW) NMR spectra. UWNMR spectra are often too broad to be uniformly excited by conventional pulse sequences that implement rectangular radiofrequency (RF) pulses. Therefore, they are typically acquired with specialized pulse sequences and frequencyswep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…Instead, in our study, a CP‐CPMG sequence (Figure 7) was used with a high RF field strength. The conditions required for a CP‐CPMG sequence to acquire UW spectra have recently been discussed by the Schurko group [24] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, in our study, a CP‐CPMG sequence (Figure 7) was used with a high RF field strength. The conditions required for a CP‐CPMG sequence to acquire UW spectra have recently been discussed by the Schurko group [24] …”
Section: Resultsmentioning
confidence: 99%
“…The conditions required for a CP-CPMG sequence to acquire UW spectra have recently been discussed by the Schurko group. [24] Based on this study, the 195 Pt RF field strength used for spinlock and CPMG refocusing π/2 pulse was set to 100 kHz. This high RF field strength maintained during the CP-CPMG sequence can excite across a broad band and permits a 75-kHz RF transmitter frequency step for variable offset cumulative spectrum (VOCS) acquisition.…”
Section: Pt Dynamic Nuclear Polarization Surface-enhanced Nmr Spectroscopy (Dnp-sens)mentioning
confidence: 99%
“…[55][56][57][58][59][60] Towards this goal, various schemes have been proposed for the acquisition of wideline solid-state NMR spectra. 53,[61][62][63] DNP has been used to enhance further the sensitivity of wideline solid-state NMR experiments under static 46,[64][65] and moderate magic angle spinning (MAS) conditions. 49 However, these methods offer poor 195 Pt NMR resolution.…”
Section: Introductionmentioning
confidence: 99%
“…21 Recently, Altenhof et al demonstrated the use of MAS CPMG experiments for the acquisition wideline spectra. 22 Fast MAS (MAS with frequencies > 30 kHz) is a powerful approach to improve the sensitivity and resolution of SSNMR spectra. [23][24][25] Notably, Lange, Nishiyama and coworkers have used fast MAS frequencies of 75 kHz to improve 119 Sn SSNMR sensitivity by focusing the intensity of 119 Sn CSA patterns into fewer sidebands.…”
Section: Introductionmentioning
confidence: 99%